2013
DOI: 10.1121/1.4807034
|View full text |Cite
|
Sign up to set email alerts
|

Speech intelligibility in hospitals

Abstract: Effective communication between staff members is key to patient safety in hospitals. A variety of patient care activities including admittance, evaluation, and treatment rely on oral communication. Surprisingly, published information on speech intelligibility in hospitals is extremely limited. In this study, speech intelligibility measurements and occupant evaluations were conducted in 20 units of five different U.S. hospitals. A variety of unit types and locations were studied. Results show that overall, no u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
(45 reference statements)
1
9
0
Order By: Relevance
“…Their study results supported the fact that decreasing the noise levels will increase the speech intelligibility [28]. These findings were echoed by Ryherd et al (2013), who concluded that none of the five hospital's twenty units showed a good average speech intelligibility rating. Nursing stations in particular recorded poor speech intelligibility ratings [29].…”
Section: Sources Of Noisementioning
confidence: 68%
See 1 more Smart Citation
“…Their study results supported the fact that decreasing the noise levels will increase the speech intelligibility [28]. These findings were echoed by Ryherd et al (2013), who concluded that none of the five hospital's twenty units showed a good average speech intelligibility rating. Nursing stations in particular recorded poor speech intelligibility ratings [29].…”
Section: Sources Of Noisementioning
confidence: 68%
“…These findings were echoed by Ryherd et al (2013), who concluded that none of the five hospital's twenty units showed a good average speech intelligibility rating. Nursing stations in particular recorded poor speech intelligibility ratings [29]. These studies clearly indicate the negative effect of hospital noise on effective communication and its impact on patient care and safety.…”
Section: Sources Of Noisementioning
confidence: 95%
“…Factors beyond speech articulation, such as intonation and rhythm, have been suggested to be at least moderately potent factors in determining intelligibility (Khan et al 2013) to some speakers (Feenaughty et al 2014). The present study additionally introduced an even higher level of control of speech amplitude in the assessments, a factor that has been highlighted recently in connection with assessments of intelligibility (Ryherd et al 2012). Thus, linguistically richer samples and greater control over confounding factors were shown here to negate the adverse effects of cZi-DBS that were observed previously in the 12 months Post-op evaluation (Johansson et al 2014).…”
Section: Discussionmentioning
confidence: 79%
“…The present study additionally introduced an even higher level of control of speech amplitude in the assessments, a factor that has been highlighted recently in connection with assessments of intelligibility (Ryherd et al. ). Thus, linguistically richer samples and greater control over confounding factors were shown here to negate the adverse effects of cZi‐DBS that were observed previously in the 12 months Post‐op evaluation (Johansson et al.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation